Can High Flow Nasal Cannula Prevent Intubation in Status Asthmaticus?”: A Case Report - Hamdani, Ihsan; Wardana, Artha Wahyu (Jurnal Komplikasi Anestesi, 2025)
Overview of the case: A 29-year-old male with status asthmaticus, the GCS score was 14, the respiratory rate was 30 x/min, SpO2 88% on room air, bilateral lung wheezing, and the blood gas analysis revealed severe respiratory acidosis. Management: Treatment involved High Flow Nasal Cannula (HFNC) oxygenation, salbutamol and ipratropium bromide nebulization, aminophylline drip infusion, and intravenous corticosteroids. Within hours, there was a significant improvement in respiratory parameters and acidosis. Subsequent monitoring in the intensive care unit showed improvement, the patient successfully being weaned off HFNC and transferred to the general ward after six days. This case highlights the efficacy of HFNC in managing severe asthma exacerbation and preventing intubation. Results: The use of HFNC, when combined with standard asthma management, has proven to be a promising option in the non-invasive management of status asthmaticus and can prevent intubation, but should be monitored carefully due to the risk of delayed escalation to respiratory support